Desafios vividos na percepção de cuidadoras de pessoas idosas dependentes - Silva, Ivanilza Carminha da (2025)
The elderly population in Brazil and worldwide is growing rapidly, contributing to an aging process that transforms the age structure of the country. This phenomenon, associated with factors such as the prevalence of chronic and degenerative diseases, can lead to limitations in the autonomy and independence of older people. The dependency of elderly individuals, whether physical or cognitive, requires specific care to meet their needs. This phenomenological study aims to understand the caregivers' perception of the challenges faced when caring for elderly dependent individuals. The project was approved by the Ethics Committee in Research with Human Beings at the State University of Feira de Santana, according to opinion No. 6.745.183. The study was conducted at a Long-Term Care Institution for the Elderly in the interior of Bahia. The study involved 12 caregivers of elderly individuals, both formal and informal caregivers, and data was collected in August 2024 through phenomenological interviews guided by Maurice Merleau-Ponty's theoretical framework. The data analysis followed the Situated Phenomenon proposal by Martins and Bicudo. From the analysis, five empirical categories emerged: Caregivers' perceptions about the process of caring for dependent elderly people; The actions and practices involved in caring for elderly people; Family participation in the process of caring for elderly people; Perceptions about the challenges faced in the caregiving process for dependent elderly people; Promotion of quality care. The results revealed that caregivers perceive caregiving as involving emotional dimensions and deep relationships. The main challenge reported by caregivers was the lack of support from families, as well as the difficulty of sharing the responsibilities inherent in caregiving, which results in physical and emotional overload for caregivers who are forced to neglect aspects of their own lives, thus increasing the risks of physical and mental illness. Another challenge highlighted was the management of multiple pathologies and the illness process of elderly individuals, associated with the financial fragility faced by families. For quality care to be provided, caregivers pointed out the need for qualification, especially for family caregivers who take on this role without any prior training. In the context of Long-Term Care Institutions for the Elderly, the need for a redesign of work teams was revealed, aiming to educe the overload of activities. The need for interdisciplinary follow-up was emphasized, integrating families and care teams to ensure qualified and comprehensive care. It is concluded that caregivers of elderly individuals face multiple challenges in performing their duties and lack adequate support from families, health teams, and social services. Given this reality, the development and implementation of public policies that provide effective support to families with dependent elderly people is essential, considering the high care demands and financial costs involved. As a product of this study, a manual for caregivers of elderly people was created,with the aim of guiding caregivers and families in promoting safer and higher-quality care.